MAINTAINING LOCAL LANGUAGE SUSTAINABILITY IN THE GLOBAL COMMUNICATION ERA - Susanti, Santi; Sukaesih, Sukaesih; Perdana, Fitri (Research And Innovation In Language Learning (RILL), 2018)
Globalization synonymous with changes in all sociocultural aspects of human life, including languages. The use of local languages as a medium of communication shifted by the national language and English that became dominant. The local language seems to be a rare item, as it is not easy to find families who teach local languages to their children. Attempts to maintain the local language never stop. One of them is through writing. A number of writers in Bandung still write in Sundanese, although quantitatively, the readers are few. This study aims to reveal the motives of 8 writers produce writing in Sundanese and how their efforts to keep generating ideas for their writing. Based on the qualitative-phenomenology method used, this study reveals, the motives of the writers to produce works in Sundanese is the idealism as individuals born and raised in the Sundanese society. They feel they have a responsibility to maintain the existence of Sundanese in the community of native speakers. To keep writing on, they do not rely on personal experience as the idea. They also made an adaptation to the information technology by using social media to spread Sundanese language writings broadly.Keywords: globalization; Sundanese; Sundanese writer; idealism; social media; preservation.